Understanding Fluid Flow during Tectonic Reactivation: An Example from the Flamborough Head Chalk Outcrop (UK) - O. Faÿ-Gomord; C. Allanic; M. Verbiest; R. Honlet; F. Champenois; M. Bonifacie; C. Chaduteau; S. Wouters; P. Muchez; E. Lasseur; R. Swennen (Geofluids)
Flamborough Head chalks are located at the extremities of E-W and N-S trending fault systems along the Yorkshire coast (UK). Rock deformation is expressed in Selwicks Bay where a normal fault is exposed along with a high density of calcite veins. The fault mineralization is tested using geochemistry. Crosscutting relationships are used to differentiate between three vein generations: a network of parallel veins that are oriented perpendicular to stratigraphy (Group I), hydraulic breccia with typical jigsaw puzzle structure (Group II), and a third generation of calcite veins crosscutting the two previous generations (Group III). Geochemical analyses revealed that all three generations possess the same chemical signature and must reflect successive pulses from the same mineralizing fluid source. Strontium isotope analyses showed that the veins have elevated 87Sr/86Sr ratios, that is, up to 7.110, while ratios of the chalk matrix equal 7.707. The latter value is in agreement with the signature of Late Cretaceous seawater. Consequently, the source of the fluid is external, reflecting an open system. The radiogenic Sr-isotope ratios, combined with low iron concentration, suggest that fluids migrated through sandy deposits. Fluid inclusion salinities range from 0 to 12 eq. wt% NaCl equiv. with a dominance of very low salinity inclusions, reflecting a meteoric signal. This leads to a model where meteoric fluids stored in an underlying confined sandstone aquifer were remobilized. The wide range of salinities could result from mixing of the meteoric fluid with some more saline fluids present in the rock sequence or from the dissolution of salts in the subsurface. In addition to the understanding of the local paragenetic evolution of the veining in Flamborough Head chalks, this study offers an insight into the way how fluid flows and mineralizes along fault zones.